Krasnaia ploshchad' - 1 - Kubaev, Rauf (Russia : President Film, 2004)
The first four episodes of the TV series, an adaptation of Eduard Topol's novel.. The film's opening scene shows the Chief deputy of the Soviet KGB, general Vigun immediately after an unpleasant talk with the Chief Party secretary Suslov. Vigun is on his way to Brezhnev's dacha intending to report some secret information. His car is halted on the motorway by a traffic jam imitated by the Suslov's people. Vigun manages to escape from the surveilance, returns to his Moscow flat and is found dead shortly after. The official Soviet media report his death to had been caused by a grave illness, which does not seem like a credible version for people who knewVigun.
Duration: 02:56:00
Keywords: Russia